Landscapes as Narrative Commentary in Cormac McCarthy’s Blood Meridian or the Evening Redness in the West - Dianne C. Luce (European Journal of American Studies)
This study argues that in Blood Meridian (1985) McCarthy creates landscape scenes that function as narrative commentary on the Glanton gang’s Indian-fighting, on America’s pursuit of Manifest Destiny, and on humanity’s innate aptitude for violence. The article surveys the biographical evidence for McCarthy’s interest in the visual arts, then inventories the language of art in Blood Meridian and explores the novel’s allusions to specific artworks. It culminates in readings of several scenes in which the narrator interprets the landscape before him in moments of sober contemplation. Each of these scenes bears a title reminiscent of painted landscapes, such as “Under the Animas peaks” or “Night scene with moon, blossoms, judge.” Each comprises a static composition that slows the violent action and also functions as a prose poem, rich in allusiveness. Evoking in the reader the perceptual and interpretive modes of a pensive viewer of a painted landscape, these scenes invite us to apply techniques drawn from art criticism to comprehend them as the narrator’s sober meditations on the Glanton gang’s violent enterprise.